Analysis of Rashomon Effects on government policy regarding redenomination and sanering - Sweetly Mumu; Winstor Muloke; Alfian Maase (University of Merdeka Malang, 2019)
Redenomination can be understood as sanering which can cause significant economic turmoil. This understanding affects the way of view or public perception of government policy in implementing its policies. Differences in perception or perspective are known as Rashomon effects. The purpose of this study is to determine the effect of Rashomon effects on government policies regarding redenomination and sanering. The sample of this study consisted of 133 respondents. Samples are determined by stratified random sampling techniques and data collection using directly distributed questionnaires. The method of data analysis is a simple linear regression. The results showed that the Rashomon effect had a significantly positive effect on redenomination and sanering. The greater the difference in understanding redenomination and sanering, the greater the public's misperception in supporting government policy and will have an impact on public readiness for government policies to simplify the Rupiah value. The implication is that the government and Bank Indonesia must disseminate to the public about the redenomination and sanering policies intensively and consistently to provide clear information to the public.JEL Classification: G31, G32, G34DOI: https://doi.org/10.26905/jkdp.v23i1.2533